VO2 Steady State at and Just Above Maximum Lactate Steady State Intensity - Bräuer, Elisabeth K.; Smekal, Gerhard (International Journal of Sports Medicine, 2020)
Over recent decades the association between metabolic and gas exchange parameters during exercise has become evident. Different “thresholds” (such as lactate thresholds, critical power, EMG thresholds) and intensity domains appear to be linked to an upper limit of oxygen uptake steady state (V̇O2SS). The aim of this study was to investigate whether MLSS is associated with the upper limit for a V̇O2SS. Forty-five subjects underwent one incremental test and 4–6 30-minute MLSS tests on a cycle ergometer. A three-component model was used to describe V̇O2 response at PMLSS and just above PMLSS+1. To evaluate the results, breath-by-breath V̇O2 and lactate (LA) values were analyzed using the intraclass correlation coefficient (ICC), increasing (k-) values and the Wilcoxon test. According to the calculated k-values of LA and VO2 at PMLSS and PMLSS+1, no significant increase of VO2 occurred during both intensities (PMLSS and PMLSS+1) from minute 10 to minute 30, confirming the existence of a V̇O2SS. Additionally, the ICC of 0.94 confirmed high accordance of the VO2 kinetics at both intensities (PMLSS and PMLSS+1). This study shows that power output at MLSS workload does not represent an accurate cut for an upper limit of V̇O2SS.
Keywords: maximum lactate steady state; MLSS; oxygen uptake steady state; VO2; steady state; maximal metabolic steady state; anaerobic threshold